Reliability of Heart Rate Measures during Walking before and after Running Maximal Efforts - Boullosa, D. A.; Barros, E. S.; del Rosso, S.; Nakamura, F. Y.; Leicht, A. S. (International Journal of Sports Medicine, 2014)
Previous studies on HR recovery (HRR) measures have utilized the supine and the seated postures. However, the most common recovery mode in sport and clinical settings after running exercise is active walking. The aim of the current study was to examine the reliability of HR measures during walking (4 km · h−1) before and following a maximal test. Twelve endurance athletes performed an incremental running test on 2 days separated by 48 h. Absolute (coefficient of variation, CV, %) and relative [Intraclass correlation coefficient, (ICC)] reliability of time domain and non-linear measures of HR variability (HRV) from 3 min recordings, and HRR parameters over 5 min were assessed. Moderate to very high reliability was identified for most HRV indices with short-term components of time domain and non-linear HRV measures demonstrating the greatest reliability before (CV: 12–22%; ICC: 0.73–0.92) and after exercise (CV: 14–32%; ICC: 0.78–0.91). Most HRR indices and parameters of HRR kinetics demonstrated high to very high reliability with HR values at a given point and the asymptotic value of HR being the most reliable (CV: 2.5–10.6%; ICC: 0.81–0.97). These findings demonstrate these measures as reliable tools for the assessment of autonomic control of HR during walking before and after maximal efforts.
Keywords: autonomic nervous system; parasympathetic reactivation; sympathetic withdrawal; heart rate complexity; detrended fluctuation analysis